1977
DOI: 10.1139/z77-022
|View full text |Cite
|
Sign up to set email alerts
|

Influence of salinity on ultrastructure of the secretory cells of the adenohypophyseal pars distalis in yearling coho salmon (Oncorhynchus kisutch)

Abstract: NAGAHAMA, Y., W. C. CLARKE, and W. S. HOAR. 1977. Influence of salinity on ultrastructure of the secretory cells of the adenohypophyseal pars distalis in yearling coho salmon (Oncorhynchus kisutch). Can. J. Zool. 55: 183-198. Six different types of secretory cells were identified by light and electron microscopy in the adenohypophyseal pars distalis of yearling coho salmon acclimated to fresh or salt water. Prolactin cells are markedly more active in the freshwater than the seawater fish; these cells exhibit d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1979
1979
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…In contrast, many reports have demonstrated that GH plays an important role in seawater adaptation (Naga- et al 1977;Yada and Hirano 1992). Therefore, the early appearance of GH in brackishwater teleosts indicates that GH plays an important role in osmoregulation in brackishwater teleosts as it does in seawater teleosts.…”
Section: Discussionmentioning
confidence: 92%
“…In contrast, many reports have demonstrated that GH plays an important role in seawater adaptation (Naga- et al 1977;Yada and Hirano 1992). Therefore, the early appearance of GH in brackishwater teleosts indicates that GH plays an important role in osmoregulation in brackishwater teleosts as it does in seawater teleosts.…”
Section: Discussionmentioning
confidence: 92%
“…It is presumed that this reduction in plasma GH is indicative of reduced secretion and not increased tissue uptake. Histological studies (Nagahama et al 1977;Nishioka et al 1982) demonstrate increased synthetic and secretory activity in somatotrope cells in seawater coho smolts. That the inhibitory action of SRIF injected intraperitoneally lasts for at least 12 h demonstrates that this procedure provides an excellent model for examining GH effects in the early stages of seawater adaptation, such as possible osmoregultory actions (Sweeting and McKeown, unpublished observations).…”
Section: Discussionmentioning
confidence: 98%
“…The interrenal and thyroid glands appear hypoactive in the stunts Bern, 1978) and coho with low plasma thyroxine in fresh water exhibit poor growth and undergo parr-reversion in seawater (Folmar & Dickhoff, 1978); the relationship between a thyroxine ' surge ' and successful adaptation and growth in seawater requires further evaluation (Dickhoff, Folmar & Gorbman, 1978). The GH cells of the pituitary of coho stunts appear more heavily granulated than those of normal coho which may indicate a reduction in GH secretion and/or an increased rate of GH synthesis (Nagahama, Clarke & Hoar, 1977). The results of the present study suggest that this alteration in GH cell activity may be induced by diminished GH-binding to GH receptors involved at some point in the feedback regulation of pituitary GH secretion.…”
Section: Discussionmentioning
confidence: 99%